Generic realignments in Maxillariinae (Orchidaceae) - Blanco, Mario A (2007)
A recent phylogenetic analysis of four DNA regions for ca. 354 species of core Maxillariinae strongly indicate that the genus Maxillaria, as traditionally circumscribed, is grossly polyphyletic. We present a new phylogenetic classification for core Maxillariinae that recognizes 17 genera. Necessary realignments include: 1) resurrection of the genera Camaridium, Heterotaxis, and Ornithidium; 2) recognition of the recent segregates Brasiliorchis (=Maxillaria sect. Repentes), Christensonella (=Maxillaria sect. Urceolatae), Nitidobulbon (in press), and a recircumscribed Sauvetrea (=Maxillaria sect. Trigonae); 3) adoption of the new genera Inti (=Maxillaria sect. Polyphyllae), Mapinguari, Maxillariella (=Maxillaria sections Ebulbes and Erectae), and Rhetinantha; 4) transfers from Maxillaria sect. Reflexae to Ornithidium, and Maxillaria sect. Rufescens to Mormolyca; and 5) synonymizing of the genera Adamanthus, Pseudomaxillaria, Psittacoglossum, and Sepalosaccus (under Camaridium), Anthosiphon (under Cryptocentrum), Chrysocycnis (under Mormolyca), Dicrypta, Marsupiaria, and Pentulops (under Heterotaxis), and Laricorchis, Neo-urbania, and Siagonanthus (under Ornithidium). Some new synonyms at the specific level are also presented.